(untitled) (Bulletin of Pure and Applied Sciences-Chemistry, 2020)
The role of metals in organic synthesis has been well known from the beginning of the development of synthetic procedure in organic Chemistry. Heterocyclic complexes have attracted increasing interest because of their role in the understanding of molecular process occurring in biochemistry and coordination chemistry. The Nitrogen donor aromatic ligand constitutes an important and interesting class of drugs / dyes not only for synthetic investigation but also for their usefulness to resist diseases. Colloidal systems are extremely wide spread in nature and are of great practical importance in our daily life. Surfactants are very useful in modern engineering and pharmaceuticals due to formation of micelles in solutions and high surface activity. Present work has been initiated with a view to obtain a profile as to the nature and structure of complex of phenothiazine with zinc oleate in different non-aqueous solvents that are of great significance in explaining their characteristics under different conditions. The present work reveals synthesis of zinc soap and its complex with phenothiazine ligand. For this synthesis the para substituted aniline was selected as the most suitable initial compound. An analytical and spectral study (IR, NMR) of this complex has been done. In order to know their thermal stability, thermogravimetric analysis has been done. A biocidal activity of complex has been carried to access their comparative toxicity.